Multimodal Molecular Imaging and Identification of Bacterial Toxins Causing Mushroom Soft Rot and Cavity Disease. (30th July 2021) - Dose, Benjamin; Thongkongkaew, Tawatchai; Zopf, David; Kim, Hak Joong; Bratovanov, Evgeni V.; García‐Altares, María; Scherlach, Kirstin; Kumpfmüller, Jana; Ross, Claudia; Hermenau, Ron; Niehs, Sarah; Silge, Anja; et al.
Abstract: Soft rot disease of edible mushrooms leads to rapid degeneration of fungal tissue and thus severely affects farming productivity worldwide. The bacterial mushroom pathogen Burkholderia gladioli pv. agaricicola has been identified as the cause. Yet, little is known about the molecular basis of the infection, the spatial distribution and the biological role of antifungal agents and toxins involved in this infectious disease. We combine genome mining, metabolic profiling, MALDI‐Imaging and UV Raman spectroscopy, to detect, identify and visualize a complex of chemical mediators and toxins produced by the pathogen during the infection process, including toxoflavin, caryoynencin, and sinapigladioside. Furthermore, targeted gene knockouts and in vitro assays link antifungal agents to prevalent symptoms of soft rot, mushroom browning, and impaired mycelium growth. Comparisons of related pathogenic, mutualistic and environmental Burkholderia spp. indicate that the arsenal of antifungal agents may have paved the way for ancestral bacteria to colonize niches where frequent, antagonistic interactions with fungi occur. Our findings not only demonstrate the power of label‐free, in vivo detection of polyyne virulence factors by Raman imaging, but may also inspire new approaches to disease control. Abstract : A combination of genome mining, metabolic profiling, and imaging techniques (MALDI and UV Raman spectroscopy) provided insight into the arsenal of antifungals produced by the mushroom pathogen Burkholderia gladioli pv. agaricicola . Targeted gene knockouts and bioassays link these antifungals to prevalent symptoms of mushroom soft rot, browning, and impaired mycelium growth.